City-making from below: A call for communities of resistance and reconstruction - de Beer, Stephan; Oranje, Mark (Town and Regional Planning, 2019)
This article laments the exclusion of small, local communities, voices and visions, from participating in making the city. It makes a case for ‘small communities’ practising resistance and reconstruction in multiple ways and places. Instead of viewing such actions as naïve or a-political, it calls for an understanding of such practices as alternatives to ‘top-down’ urban processes, and, as such, representing a different and necessary, critical political imagination. In doing so, it fuses insights from equity planning theories, praxis-based liberation theological approaches, and emancipatory community development approaches. It argues that communities, aware of the forces that would seek to tear them apart, can play a significant role in making cities ‘from below’. This, it is argued, would be even more possible through such communities finding each other, and nurturing deep solidarities, until broad-based, interconnected movements take shape, embodying concrete signs of wholeness.